AB1132 EFFECTIVENESS AND SAFETY OF ULTRASOUND-GUIDED FASCIA HYDRORELEASE ON METATARSALGIA WITHOUT SONOGRAPHIC EVIDENCE OF INFLAMMATION IN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Suda, M.; Muranaka, K.; Ohde, S.; Minoda, M.
Abstract : Background: Patients with rheumatoid arthritis (RA) who have metatarsophalangeal (MTP) joint involvement sometimes complain metatarsalgia without active sonographic inflammation 1 . Treatment of non-inflammatory metatarsalgia in RA is challenging and the pain sometimes lasts for years even though systemic inflammation completely resolves. On the other hand, intervention to fascia has increasingly attracted attention as a management of non-inflammatory pain 2 . Recently, we have invented a new technique called ultrasound-guided fascia hydrorelease (UGFHR), which injects fluid into "stacking fascia" (defined as high echoic and thickened fascia, often adhering to adjacent structures), making it unglued and instantaneously improving fascial pain. Objectives: This study is aiming for prospective evaluation of effectiveness and safety of UGFHR on metatarsalgia in patients with RA. Methods: We enrolled consecutive 11 patients with RA who came to rheumatology service in Suwa Central Hospital and satisfied the following inclusion and exclusion criteria: Inclusion criteria were having at least one MTP joint pain on which the patient has tenderness on the extensor side. Exclusion criteria were positive inflammation with ultrasound evaluation (defined as gray scale (GS) ≥2 and/or power doppler scale (PDS) ≥1) or having other cause of pain such as intermetacarpal bursitis, Morton's neuroma. The patients received UGFHR on the fascia between the MTP joint capsule and the extensor tendon of the toe. We first searched for the stacking fascia between the two structures using ultrasound with longitudinal view of the extensor side of the MTP joint, and injected 2ml of normal saline into the stacking fascia, making it unglued (Fig. 1). If there was no stacking fascia, we injected on the fascia where the joint capsule and the extensor tendon became closest. Numeric rating scale (NRS) of pain on walking and tenderness on the target MTP joint was measured on 3 occasions: before, immediately after, and one week after the UGFHR. Adverse events were also recorded. The data were analyzed longitudinally, using Friedman test. Results: The characteristics of the patients are shown in table 1 . Female gender was dominant. Most of them were established RA. Simplified disease activity index (SDAI) were variable. The changes in NRS from before to immediately after and one week after the UGFHR are described in figure 2 . Pain on walking and tenderness on the target joint both significantly decreased immediately after the procedure (ΔNRS from before to immediately after the UGFHR: -3.45 (95% confidence interval (CI) -2.32 to -4.59, p=<.01) and -2.45 (95% CI -1.32 to -3.59, p=<.01) respectively), and the change was maintained until one week after the UGFHR (ΔNRS from before to one week after the UGFHR: -3.09 (95% CI -1.77 to -4.42, p=<.01) and -3.27 (95% CI -1.80 to -4.75, p=<.01) respectively. In terms of safety, 7 out of 11 patients complained injection pain, all of which did not last for a week. Otherwise, there was no adverse event such as infection, nerve injury, bleeding, or tendon rupture. Conclusion: Ultrasound-guided fascia hydrorelease on MTP joint can be an effective and safe treatment option in patients with RA who have metatarsalgia but no sonographic evidence of MTP inflammation. References: [1]Garrigues, Florent, et al. "Concordance between clinical and ultrasound findings in rheumatoid arthritis." Joint Bone Spine80.6 (2013): 597-603. [2]Kurosawa, Ayato, Tadashi Kobayashi, and Hirofumi Namiki. "Ultrasound-Guided Dry Needling for Abnormal Fascia Between the Deltoid Muscle and the Supraspinatus Tendon." Pain Medicine (2019). Disclosure of Interests: None declared